Penerapan Model Contextual Teaching Learning Berbasis Keunggulan Lokal terhadap Pemecahan Masalah Siswa Kelas V - Nurmala Kusumasari; Savitri Wanabuliandari; Ratri Rahayu (Universitas Muria Kudus, 2020)
The purpose of this study are (1) to analyze the improvement of problem solving abilities of fifth grade students before and applied contextual learning models based on local excellence, and (2) analyze the improvement of problem solving skills of fifth grade students before and apply the model to which contextual teaching based learning is applied local excellence. This research is a quantitative research with quasi-experimental design in the form of one group pretest posttest. Analysis of the data used in this study used the n-gain test. The n-gain trial which is used to study the improvement of problem solving abilities and skills in fifth grade students. Based on the results of the research that has been obtained, the results are (1) Contextual Learning based on local excellence, and (2) is a model of improving learning based on Class V problems before using the Contextual Learning model and using the Contextual Learning model based on local excellence.